The Gulf War as Simulacra: An Analysis of Vishwa Ghatana [World Affairs] on Nepal Television - Aryal, Kundan (SCHOLARS: Journal of Arts & Humanities, 2023)
Between early August 1990 and the end of February 1991, the coverage of the Persian Gulf War on Cable News Network (CNN) television showcases a comprehensive example of simulacra. Based on Jean Baudrillard's ideas of postmodern simulacra and simulation, this paper attempts to demonstrate how the simulacra of the Gulf War appeared before the Nepali audience through a domestic nationwide channel. The major source of news and perspectives of the contents of Nepal Television's world affairs program were the reports and images of CNN. The paper, with an approach to looking into the event retrospectively, demonstrates a case where CNN used a comparatively small television channel in a developing country to disseminate its cultural product to the local audience in their vernacular language. Taking Nepal Television (NTV) and its Vishwa Ghatana [World Affairs], a program dedicated to the world affairs as a case in point, this paper examines relationships between the rhetoric and reality in the theoretical and conceptual frame of simulacra and simulation based on Baudrillard’s ideas.